New Pyrolysis Mechanisms for Dust Explosion Simulation - Tima Al Haffar; Nathalie Bardin-Monnier; Maria Portarapillo; Almerinda Di Benedetto; Olivier Dufaud (Chemical Engineering Transactions)
Numerical simulation of dust explosions can be used for intensive, multi-parameter sensitivity studies, reducing the number of experimental tests required. Nevertheless, to develop such approaches, it is imperative to collect reliable input data beforehand. Preliminary tests show that particular attention needs to be paid to developing new flash pyrolysis mechanisms. Indeed, simple devolatilization reactions (polymer into monomer conversion) are not suitable, and the chemical species to be considered are far more numerous than in the case of lighter chemical compounds or shorter chains. On the other hand, the mechanical properties of synthetic polymers seem to limit their fragmentation in the 20L sphere, which could simplify the simulation approach by neglecting particle sizes modification.